Performing Arts Center - Cal Poly Public Affairs:::::::::; William B. Dewey::::::::: (1996)
Exterior detail of the Performing Arts Center on campus. Inset: A student violinist practices for her upcoming recital in the main hall of the Performing Arts Center's Christopher Cohan Center.